The impact of gender and ethnic background on physical and mental health in a post-pandemic student cohort in the UK - Jon CATLING; Emma SUTTON (Journal of Health and Social Sciences)
Introduction: The COVID-19 pandemic has had a profoundly negative impact on the population's mental health, which was most severe on young people, particularly those students studying at University. This study examines the effects of gender, age, ethnic background, physical exercise, and smartphone use on the psychological well-being of UK students in a post-pandemic setting. Methods: A cross-sectional study design was utilized. The study was conducted online, with participants studying at a Higher Education Institution within the UK. The current study sampled seven hundred and ninety-eight undergraduate students. Data was gathered through a series of anonymous questionnaires administered online. Results: We found that gender significantly impacted mental health, levels of physical exercise, and mobile phone use. Further analysis demonstrated that age, amount of exercise, and mobile phone use were significant predictors of depression, and mobile phone use was a significant predictor of anxiety. Discussion and Conclusion: Overall, we found far higher-than-expected mental health problems within the student cohort. These findings are discussed concerning potential interventions.